Acute kidney injury development in polytrauma and the safety of early repeated contrast studies: A retrospective cohort study. Issue 6 (7th December 2022) - Giles, Thomas; Weaver, Natasha; Varghese, Adrian; Way, Teagan L.; Abel, Christian; Choi, Peter; Briggs, Gabrielle D.; Balogh, Zsolt J.
Abstract : Acute kidney injury in polytrauma patients is not independently associated with repeated contrast studies during the early ICU period. Abstract : BACKGROUND: The role of repeat intravenous contrast doses beyond initial contrast imaging in the development of acute kidney injury (AKI) for multiple injury patients admitted to the intensive care unit (ICU) is not fully understood. We hypothesized that additional contrast doses are potentially modifiable risk factors for worse outcomes. METHODS: An 8-year retrospective study of our institutional prospective postinjury multiple organ failure database was performed. Adult ICU admissions that survived >72 hours with Injury Severity Score (ISS) of >15 were included. Patients were grouped based on number of repeat contrast studies received after initial imaging. Initial vital signs, resuscitation data, and laboratory parameters were collected. Primary outcome was AKI (Kidney Disease: Improving Global Outcomes criteria), and secondary outcomes included contrast-induced acute kidney injury (CI-AKI; >25% or >44 μmol/L increase in creatinine within 72 hours of contrast administration), multiple organ failure, length of stay, and mortality. RESULTS: Six-hundred sixty-three multiple injury patients (age, 45.3 years [SD, 9.1 years]; males, 75%; ISS, 25 (interquartile range, 20–34); mortality, 5.4%) met the inclusion criteria. The incidence of AKI was 13.4%, and CI-AKI was 14.5%. Multivariate analysis revealed that receiving additional contrast doses within the first 72 hours was not associated with AKI (odds ratio, 1.33; confidence interval, 0.80–2.21; p = 0.273). Risk factors for AKI included higher ISS ( p < 0.0007), older age ( p = 0.0109), higher heart rate ( p = 0.0327), lower systolic blood pressure ( p = 0.0007), and deranged baseline blood results including base deficit ( p = 0.0042), creatinine ( p < 0.0001), lactate ( p < 0.0001), and hemoglobin ( p = 0.0085). Acute kidney injury was associated with worse outcomes (ICU length of stay: 8 vs. 3 days, p < 0.0001; mortality: 16% vs. 3.8%, p < 0.0001; MOF: 42% vs. 6.6%, p < 0.0001). CONCLUSION: There is a limited role of repeat contrast administration in AKI development in ICU-admitted multiple injury patients. The clinical significance of CI-AKI is likely overestimated, and it should not compromise essential secondary imaging from the ICU. Further prospective studies are needed to verify our results. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :